Verbal memory functioning in recurrent depression during partial remission and remission-Brief report - Hammar, Åsa; Årdal, Guro (Frontiers in Psychology, 2013)
The aim of the present study was to investigate verbal memory performance in a group of patients with remitted and partial remitted major depressive disorder. Thirty-one patients and 31 healthy matched controls were included in the study. Results from the California Verbal Learning Test show intact verbal memory performance in the patient group regarding learning, recall and recognition. However, patients had significantly poorer performance compared to healthy controls in immediate recall of the first trial in the verbal memory test. In conclusion, the patient group showed intact memory performance, when material is presented more than once. These findings indicate that memory performance in MDD patients with partial remission and remission benefit from repetition of material.